2024
DOI: 10.1021/acssuschemeng.3c07514
|View full text |Cite
|
Sign up to set email alerts
|

Development of Mg-Modified Fe-Based Catalysts for Low-Concentration CO2 Hydrogenation to Olefins

Kaidi Liu,
Di Xu,
Haifeng Fan
et al.

Abstract: With mounting concerns about reducing carbon emissions, developing a catalyst that can be used in the hydrogenation of CO 2 to olefins makes sense. Considering the high cost of CO 2 capture, the direct use of low-concentration CO 2 to produce olefins is more promising. In this work, we develop a reliable Mg-modified Fe-based catalyst for the low-concentration hydrogenation of CO 2 to olefins. The optimized KFeMnMg 0.15 catalyst exhibits a high olefin yield of 15.4% with an olefin selectivity of 61.2% at a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…MgO and TiO 2 were also commonly used catalyst carriers for the preparation of low carbon olefins by CO 2 hydrogenation. The electron-donating property and surface alkalinity of MgO promoted the dissociation and adsorption of CO, limiting the hydrogenation ability of the Fe-based catalysts, while the stability of the basic sites effectively prevented the loss of the active substances and the basic sites during the reaction process, which improved the selectivity of light olefins. , XRD and CO 2 -TPD measurements showed that the (111) crystalline facets of MgO increased the surface alkalinity of the catalyst, facilitated the dissociative adsorption of CO, and accelerated the reaction rate. , The oxygen vacancies in the TiO 2 carrier help bridge the adsorption of carbonate species and promote the decomposition of carbonate species into carbon intermediates, accelerating the C–C coupling reaction …”
Section: Fe-based Catalystsmentioning
confidence: 99%
“…MgO and TiO 2 were also commonly used catalyst carriers for the preparation of low carbon olefins by CO 2 hydrogenation. The electron-donating property and surface alkalinity of MgO promoted the dissociation and adsorption of CO, limiting the hydrogenation ability of the Fe-based catalysts, while the stability of the basic sites effectively prevented the loss of the active substances and the basic sites during the reaction process, which improved the selectivity of light olefins. , XRD and CO 2 -TPD measurements showed that the (111) crystalline facets of MgO increased the surface alkalinity of the catalyst, facilitated the dissociative adsorption of CO, and accelerated the reaction rate. , The oxygen vacancies in the TiO 2 carrier help bridge the adsorption of carbonate species and promote the decomposition of carbonate species into carbon intermediates, accelerating the C–C coupling reaction …”
Section: Fe-based Catalystsmentioning
confidence: 99%